Pengaruh Self-efficacy Terhadap Burnout Dengan Resilience Sebagai Variabel Mediasi Pada Karyawan PT Sapta Sentosa Jaya Abadi Mukomuko - Rissa Eka Putri; Hendrik Heri Sandi (Pusat Riset dan Inovasi Nasional, 2025)
Burnout among employees in the palm oil processing industry is a critical issue that hinder productivity and organizational performance. This study aims to examine the effect of self-efficacy on burnout, with resilience as a mediating variable. A quantitative approach was employed, involving 90 empoloyees of PT Sapta Sentosa Jaya Abadi Mukomuko who completed a structured questionnaire. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method. The results indicate that self-efficacy has a significant negative on burnout. In addition, Self-efficacy positively influences resilience, which in turn significantly reduces burnout levels. The findings also demonstrate that resilience plays a mediating role in the relationship between self-efficacy and burnout. The results highlight the importance of strengthening self-efficacy and resilience as a effective strategies to prevent employee burnout, particularly in high demand industrial workplaces.